Malaysian ergonomics standards – its development, awareness and implementation - a review article - Mohd Yusuff, Rosnah; Baba, Zuraidah; Md. Dawal, Siti Zawiah; Tan, Evelyn (Tehran University of Medical Sciences, 2016)
Background: Ergonomics standards play an important role in product and system design as it can improve their us ability; provide comfort and safety for the users. The number of musculoskeletal diseases has increased in recent years in Malaysia. However, the awareness and importance of ergonomics in Malaysia is still very low among the industries. Many ergonomics standards have been adopted by SIRIM Berhad under the purview of Department of Standards Malaysia (STANDARDS MALAYSIA). However, the take-up has been slow. Method: This paper examined the role of SIRIM Berhad in developing the standards, involvement at international levels and other government agencies in promoting Ergonomics. Ergonomics awareness seminars were arranged in three localities, representing three regions, not only to disseminate information on ergonomics and standards available but also to solicit inputs from stakeholders on the problems in developing and adoption of the standards. Results: Most of the stakeholders were not aware of the standards, do not know how to implement it, and do not have people who are knowledgeable in ergonomics. Since it is not mandatory, no conscious efforts were directed towards it. The lack of research in the various areas has also hindered the development of MS standards. Conclusion: Standards are important in determining at least the minimum requirement for safety, health and comfort of workers. Creating awareness on the importance of ergonomics should be given some priority and this can be seen by the recent encouraging developments in Malaysia in the field of Ergonomics.